2012
DOI: 10.1515/znc-2012-5-610
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Genotoxicity of the Pyrethroid Pesticide β-Cyfluthrin Using the Comet Assay in the Fish Bryconamericus iheringii

Abstract: Environmental pollution by pesticide residues is a major environmental concern due to the extensive use of these substances in agriculture. The insecticide β-cyfl uthrin is a synthetic pyrethroid widely used in agricultural and other domestic activities. The aim of the present study was to assess the genotoxic effects of a sublethal exposure of the fi sh Bryconamericus iheringii (Characidae) to a commercial formulation of β-cyfl uthrin using the comet assay. Fish were exposed to sublethal concentrations (4.2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Furthermore, exposure to multiple stressors decreases the ability to physiologically cope with these highly toxic, endocrine active compounds . While some of the studies discussed above use concentrations higher than those commonly measured in the environment, many are consistent with pyrethroid concentrations detected in aquatic habitats, known to range from ng/g in sediments to ng−μg/L in the water column. ,,,, Notably, concentrations in suspended sediments have been measured in the mg/L range following storms . It is also important to consider that these concentrations may not be representative of those that are actually bioavailable, since pyrethroids have been demonstrated to bioconcentrate in animal tissues possessing ng−μg/g levels. , Furthermore, much work remains to better determine safe levels in the context of multiple stressors, pyrethroid mixtures, metabolites, and the potential for bioconcentration/bioaccumulation, and to develop analytical approaches sufficient to consistently detect pyrethroid presence in water, sediment, and tissues at ng/L and ng/g levels and below, particularly given that pyrethroid usage is on the rise globally .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Furthermore, exposure to multiple stressors decreases the ability to physiologically cope with these highly toxic, endocrine active compounds . While some of the studies discussed above use concentrations higher than those commonly measured in the environment, many are consistent with pyrethroid concentrations detected in aquatic habitats, known to range from ng/g in sediments to ng−μg/L in the water column. ,,,, Notably, concentrations in suspended sediments have been measured in the mg/L range following storms . It is also important to consider that these concentrations may not be representative of those that are actually bioavailable, since pyrethroids have been demonstrated to bioconcentrate in animal tissues possessing ng−μg/g levels. , Furthermore, much work remains to better determine safe levels in the context of multiple stressors, pyrethroid mixtures, metabolites, and the potential for bioconcentration/bioaccumulation, and to develop analytical approaches sufficient to consistently detect pyrethroid presence in water, sediment, and tissues at ng/L and ng/g levels and below, particularly given that pyrethroid usage is on the rise globally .…”
Section: Discussionmentioning
confidence: 89%
“…However, cyfluthrin does retard amphibian larval growth, resulting in smaller larvae undergoing metamorphosis . Additionally, Marinowic et al reported that beta-cyfluthrin causes DNA damage (strand breakage measured via Comet assay) in fish found in stagnant waters ( Bryconamericus iheringii ) at exposure levels of 5.6 μg/L, which are reportedly environmentally relevant in Brazil.…”
Section: Cyfluthrinmentioning
confidence: 99%
“…and in vivo studies have shown that pyrethroids may induce genotoxicity and oxidative stress by promoting the formation of reactive oxygen species [59][60][61]. Animal studies have reported that prenatal exposure to pyrethroids may impair development of the testes and epididymides, decrease the number of epididymal spermatozoa in adult male offspring, disrupt spermatogenesis, and decrease testosterone synthesis by downregulating the expression of testicular StAR [62,63].…”
Section: Exposure To Parabens and Semen Qualitymentioning
confidence: 99%
“…Considering that B. iheringii is omnivorous, the literature shows that this species has a great potential for metal bioaccumulation, often in greater amounts compared to carnivorous fishes, for example (Yousafzai, Chivers, Khan, Ahmad, & Siraj, 2010). Additionally, several biomarkers have been evaluated in this species, such as histological (Dalzochio et al, 2019) and genotoxic (Marinowic, Mergener, Pollo, Maluf, & Silva, 2014;Caetano, Oliveira, & Zawadadzki, 2016;Dalzochio et al, 2019).…”
Section: Introductionmentioning
confidence: 99%